2019
DOI: 10.1590/s1980-6574201800040050
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic preconditioning delays the time of exhaustion in cycling performance during the early but not in the late phase

Abstract: Aims: To investigate the early and late ischemic preconditioning (IPC) effect on the trained cyclists' performance during incremental cycling test until exhaustion. Methods: Twenty-one male cyclists allocated to an IPC (2 x 5-min of blood flow occlusion at 50 mm Hg above systolic pressure followed + 5-min of deflation), SHAM (2 x 5-min at 20 mm Hg) or control (CON; no occlusion) interventions, performed three incremental cycling test (ICT) until exhaustion on separate days. The ICT were conducted pre intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…The incremental cycling test is often used in research to evaluate psychophysiological responses 11,24 which are highly correlated with cycling performance 11 . However, for greater accuracy in correlation analysis, especially in laboratory studies, the indices of aerobic fitness should be normalized to BM.…”
Section: Discussionmentioning
confidence: 99%
“…The incremental cycling test is often used in research to evaluate psychophysiological responses 11,24 which are highly correlated with cycling performance 11 . However, for greater accuracy in correlation analysis, especially in laboratory studies, the indices of aerobic fitness should be normalized to BM.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the responsiveness of IR intervention, when applied before exercise or test to improve performance, has been associated with the training level of the subjects. Specifically, it was demonstrated that participants with low fitness level presented large [ 35 ] while high training level small [ 19 ] or no response to this intervention [ 36 ]. In this context, since PEIC responses have the same pattern, it could be speculated that its responses are also dependent on the fitness level of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Only one study analyzed two different protocols [ 6 ]. While some authors using a total time of ischemia above 10 min described positive effects on recovery [ 7 , 29 , 35 ], others using shorter time did not [ 27 , 28 ]. Although Beaven et al [ 24 ] found positive results for PEIC using total time of 6 min, in this investigation subjects were recreational athletes.…”
Section: Discussionmentioning
confidence: 99%
“…12 O PCIR é uma estratégia não invasiva e de fácil aplicação que pode promover a melhora do desempenho do exercício. 13,14 Dessa forma, o objetivo deste estudo é investigar o efeito do pré-condicionamento isquêmico remoto no consumo máximo de oxigênio (VO2máx) e potência máxima (Wmáx) em corredores e ciclistas.…”
unclassified